Social Capital and Democratic Governance: Strengthening Public Trust in Contemporary Society - Ahmad Abu Sufyan (Al-Qalam Institue, 2025)
Social capital has become an increasingly important element in strengthening democratic governance amid growing political polarization, declining institutional trust, and rapid digital transformation. This study aims to examine the role of social capital in reinforcing democratic governance by synthesizing contemporary scholarly literature on public trust, civic participation, collaborative governance, social cohesion, and digital resilience. The study employed a Systematic Literature Review (SLR) approach using the PRISMA framework. Relevant articles published in reputable international databases were identified, screened, assessed for eligibility, and analyzed through thematic synthesis to identify recurring concepts, theoretical perspectives, and governance patterns. The findings reveal five interconnected themes: social capital as the foundation of democratic governance, public trust and institutional legitimacy, civic participation and collaborative governance, digital society and democratic resilience, and the development of an integrated conceptual framework. The synthesis demonstrates that social capital functions as a strategic governance resource by strengthening interpersonal trust, enhancing institutional legitimacy, promoting collaborative policymaking, fostering social cohesion, and supporting democratic resilience in digitally connected societies. The study concludes that sustainable democratic governance cannot rely solely on institutional reforms or technological advancement but requires continuous investment in trust-based social relationships, ethical leadership, civic education, and inclusive governance practices. The proposed integrated conceptual framework contributes to democratic governance literature by linking sociological, organizational, educational, and technological dimensions into a comprehensive model. The findings provide practical implications for policymakers, educational institutions, and civil society organizations seeking to strengthen democratic governance through collaborative, transparent, and trust-based governance systems.